Pengaruh Hypnobirthing Terhadap Penurunan Nyeri pada Ibu Intranatal Kala I - Mayang Wulan; Nuriah Arma; Utary Dwi Listiarini (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2022)
ABSTRACT Background: The World Health Organization (WHO) reports that every year more than 200 million pregnant women, most pregnancies end in the birth of live babies to healthy mothers, even though in some cases, birth is not a happy event but becomes a comfortable period. They fill with pain, fear, suffering, and even death. Hypnobirthing is carried out for mothers in labor to create calm conditions for the mother to reduce tension and anxiety and minimize pain during delivery. This study aims to determine the effect of hypnobirthing on reducing pain in mothers in the first stage of labor. Method: This research design is quantitative research, where the research design used is Quasi Experiment with Pre test-Post test Design without a control group. The sample for this research was mothers giving birth in the 1st stage in June-August 2022 at BPS Irawati using a minimum experimental sample size of 15 mothers giving birth. The sampling technique was purposive sampling. Data analysis by univariate analysis test, bivariate analysis test Wilcoxon Test. Result: The results of the study, before being given hypnobirthing, nine people experienced unbearable pain, and six people weighed. Whereas the mothers who gave hypnobirthing experienced mild pain, 13 people and two had moderate pain. Based on the results of the Wilcoxon Signed Rank Test calculation, the p-value is 0.001.There is an effect of hypnobirthing on reducing birth pain in mothers in the first stage. It recommends that midwives apply hypnobirthing in the care of birthing mothers to reduce labor pain. Keyword: Hypnobirthing, Pain, Intranatal 1st Stage